(untitled) (INMR - Innovation & Management Review, 2014)
This paper discusses the management of the technology transfer process conducted by a Technology Transfer Office (TTO) of a federal public university. Patent co-authorship and multidisciplinarity were used as concepts to evaluate and monitor the quality of academic and practical contribution and their potential for commercial application, using descriptive statistics and cluster analysis. Considering only multidisciplinary patents, binary cluster analysis was conducted, using Jaccard similarity measurement and single linkage method to determine proximity among academic units. Apart from the analysis of the number of patents, the approach enabled discussions and questions regarding the differences between patent generation patterns, resultant from the specific organizational culture and structures. The discussions are relevant to improve the identification of opportunities in technology transfer processes by the TTO.